Prediction of optimal continuous positive airway pressure in Thai patients with obstructive sleep apnea - Narongkorn Saiphoklang; Kanyada Leelasittikul; Apiwat Pugongchai (Scientific Reports, 2021)
Abstract Continuous positive airway pressure (CPAP) is simple and effective treatment for obstructive sleep apnea (OSA) patients. However, the CPAP prediction equation in each country is different. This study aimed to predict CPAP in Thai patients with OSA. A retrospective study was conducted in Thai patients, who OSA was confirmed by polysomnography and CPAP titration from January 2015 to December 2018. Demographics, body mass index (BMI), neck circumference (NC), Epworth sleepiness scale, apnea–hypopnea index (AHI), respiratory disturbance index (RDI), mean and lowest pulse oxygen saturation (SpO2), and optimal pressure were recorded. A total of 180 subjects were included: 72.8% men, age 48.7 ± 12.7 years, BMI 31.0 ± 6.3 kg/m2, NC 40.7 ± 4.1 cm, AHI 42.5 ± 33.0 per hour, RDI 47.1 ± 32.8 per hour, and lowest SpO2 77.1 ± 11.0%. Multiple linear regression analysis identified NC, BMI, RDI, and lowest SpO2. A final CPAP predictive equation was: optimal CPAP (cmH2O) = 4.614 + (0.173 × NC) + (0.067 × BMI) + (0.030 × RDI) − (0.076 × lowest SpO2). This model accounted for 50.0% of the variance in the optimal pressure (R2 = 0.50). In conclusion, a CPAP prediction equation can be used to explain a moderate proportion of the titrated CPAP in Thai patients with OSA. However, the CPAP predictive equation in each country may be different due to differences of ethnicity and physiology. Trial registration: TCTR20200108003.